2021
DOI: 10.1002/dc.24837
|View full text |Cite
|
Sign up to set email alerts
|

Application of the International System for Reporting Serous Fluid Cytopathology in routine reporting of pleural effusion and assessment of the risk of malignancy

Abstract: Introduction:The International System for Reporting Serous Fluid Cytopathology (ISRSFC) was proposed by the International Academy of Cytology and the American Society of Cytopathology.Aim of the study: We have applied this system for reporting of pleural effusion cytology and report our experience.Materials and Methods: All the pleural effusions from January 2019 to June 2020 were retrieved from the database. All these cases were reviewed and recategorized according to the proposed system of 5 categories: non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
47
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(59 citation statements)
references
References 18 publications
8
47
4
Order By: Relevance
“…Pericardial effusions only included three cases, and their distribution was 33.33% (one case) NFM and 66.67% (two cases) MAL. Our results are compatible with those of other studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], some of which include only pleural effusions [ 25 , 26 , 27 , 30 ], while others include pleural and peritoneal effusions [ 24 , 28 , 31 , 32 ], and one includes only pericardial effusions [ 29 ]. In regard to pleural effusions, the rate of malignancy reported from oncologic centers is significantly higher [ 31 ], while a similar rate to ours is reported from other institutions [ 26 ], probably related to the “general” nature of our institution.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Pericardial effusions only included three cases, and their distribution was 33.33% (one case) NFM and 66.67% (two cases) MAL. Our results are compatible with those of other studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], some of which include only pleural effusions [ 25 , 26 , 27 , 30 ], while others include pleural and peritoneal effusions [ 24 , 28 , 31 , 32 ], and one includes only pericardial effusions [ 29 ]. In regard to pleural effusions, the rate of malignancy reported from oncologic centers is significantly higher [ 31 ], while a similar rate to ours is reported from other institutions [ 26 ], probably related to the “general” nature of our institution.…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, for peritoneal effusions, the corresponding values were 80%, 99.3%, 98.5% and 89.6%. The accuracy parameter values are in line with those reported in other studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Notably, oncologic centers report lower sensitivity [ 25 , 31 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Early reports utilizing the system have suggested that it is user friendly, but criteria defining various categories should be further extended and better defined for the system to be more effective. 1 In an effort to define interobserver reproducibility for the TIS, we conducted a study of interobserver agreement using the definitions and criterial published in the TIS monograph. 2 Each of the cytopathologists reviewed the TIS monograph before commencing specimen review.…”
mentioning
confidence: 99%